(untitled) - Sa’diyah, Afifatus; Sopiyani, Lia (JP2KG AUD (Jurnal Pendidikan, Pengasuhan, Kesehatan dan Gizi Anak Usia Dini), 2024)
This research aims to produce a learning media called MABANA to stimulate the religious and moral development of children aged 4-5 years. There are short chapters of the Qur’an, daily prayers, good and bad behavior, various religions in Indonesia, the pillars of Islam and the pillars of faith, as well as mandatory prayer intentions and movements. The purpose of this research is to determine the feasibility level of the MABANA Islam application based on material expert validation and media expert validation. Knowing the level of children’s response to the MABANA Islam application based on children’s responses. The type of research used is ADDIE model development research (Analysis, Design, Development, Implementation, and Evaluation). The research uses five steps including problem analysis, design, development, implementation, and evaluation. The subjects in this study were experts and 4-5 year old children of RA Al-Amanah and RA Muslimat NU II Al-Bashor. Data collection techniques in the study were interviews, questionnaires (validation of material experts, media experts, and children’s responses), and documentation. Based on the results of this study, it can be concluded that the value obtained from the Islamic MABANA application media is from material experts of 86.15% with a very high predicate or very feasible to use, learning media experts of 81.05% with a high predicate or feasible to use, small group trials of 76.12% with a very high predicate or very feasible to use, and field trials of 78.33% with a very high predicate or very feasible to use.